2006
DOI: 10.1038/sj.ijo.0803338
|View full text |Cite
|
Sign up to set email alerts
|

The association of SNP276G>T at adiponectin gene with circulating adiponectin and insulin resistance in response to mild weight loss

Abstract: Objective: The purpose of this study was to determine whether common single nucleotide polymorphisms (SNPs) at the adiponectin (ADIPOQ) locus influence changes in circulating adiponectin and the features of insulin resistance in response to a weight loss intervention. Subjects: In total, 294 nondiabetic/overweight-obese Koreans participated in a clinical intervention study lasting 12 weeks involving a caloric reduction of À300kcal/day. Methods: Plasma adiponectin, blood lipids, glucose and insulin concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
4
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 25 publications
4
20
4
1
Order By: Relevance
“…However, significant reductions in insulin resistance and increases in adiponectin concentration during weight loss have been observed (Haluzík et al, 2004), and the same results have been found only in patients with the GG genotype but not in T-allele carriers in overweight or obese Koreans (Shin et al, 2006). Furthermore, T allele was related to coronary artery disease risk in Italians (Filippi et al, 2005) and TT genotype was associated with cardiovascular disease risk in a subsample of our study population (Yu et al, 2007).…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…However, significant reductions in insulin resistance and increases in adiponectin concentration during weight loss have been observed (Haluzík et al, 2004), and the same results have been found only in patients with the GG genotype but not in T-allele carriers in overweight or obese Koreans (Shin et al, 2006). Furthermore, T allele was related to coronary artery disease risk in Italians (Filippi et al, 2005) and TT genotype was associated with cardiovascular disease risk in a subsample of our study population (Yu et al, 2007).…”
Section: Resultssupporting
confidence: 48%
“…in Korea reported significantly higher serum adiponectin in non-diabetic patients with the TT genotype than in those with the GG or GT genotype (Shin et al, 2006;Jang et al, 2008). However, significant reductions in insulin resistance and increases in adiponectin concentration during weight loss have been observed (Haluzík et al, 2004), and the same results have been found only in patients with the GG genotype but not in T-allele carriers in overweight or obese Koreans (Shin et al, 2006).…”
Section: Resultsmentioning
confidence: 51%
“…Numerous articles have speculated on how the ability to identify an individual's susceptibility to diet-related diseases at an early stage, coupled with diet and lifestyle information focused on known diet-genotype-disease interactions, could increase understanding of the relationship between diet and human health [1, 17, 35, 37, 43, 46-48, 50, 52]. Genotyping of individuals participating in dietary intervention studies was rapidly incorporated into study protocols [7,24,42,50,55] as well as into many of the large ongoing cohort studies which are investigating potential diet-health relationships through observational associations [48,58].…”
Section: Genetic Variation and Nutritionmentioning
confidence: 99%
“…However, this study only assessed the genetic influence on IR using HOMA-IR under a codominant model and not the genetic influence on blood glucose. Furthermore, other studies [13,16,19,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] regarding the association between the ADIPOQ T45G polymorphism and IR have been reported.…”
Section: Discussionmentioning
confidence: 99%